Accumulation of 2-methylcitrate induces metabolic imbalance in Bacillus thuringiensis, revealing a detoxification strategy mediated by an internal promoter - Du, Cuiying; Zheng, Lanteng; Fu, Ke; Wang, Rui; Liu, Zhuofan; Liang, Fengxian; Zeng, Chenyi; Zhou, Xuanmingyue; Yang, Tingting; Dai, Yujun; Xin, Bingyue; Zheng, Cao (Frontiers in Microbiology, 2026)
Propionic acid is a common food preservative, but many microbes, including the important biocontrol agent Bacillus thuringiensis, can metabolize it via the 2-methylcitrate cycle. However, the accumulation of cycle intermediates, such as 2-methylcitrate, can be toxic, and the overall physiological effects of this toxicity on B. thuringiensis are unclear. In this study, we investigated the toxic effects of 2-methylcitrate on B. thuringiensis and its corresponding cellular responses by characterizing the prpD deletion mutant ΔprpD, which lacks the 2-methylcitrate dehydratase. We found that the accumulation of 2-methylcitrate in the ΔprpD mutant led to a sharp decline in biomass, extensive cell lysis and death during the stationary phase. Comparative transcriptomic analysis revealed that this toxicity is associated with severe overall metabolic imbalance, characterized by a significant transcriptional dichotomy: concerted downregulation of nearly all glycolytic pathway genes and simultaneous upregulation of TCA cycle genes. This transcriptional decoupling of central carbon metabolism is the root cause of the observed lethal phenotype. Furthermore, we identified and characterized an internal promoter located within the prp operon that specifically drives prpD expression. This internal promoter rapidly and efficiently clears toxic intermediates, representing a complex regulatory adaptation mechanism to combat the harmful effects of propionic acid metabolism. Our findings provide a comprehensive transcriptional view of the toxicity of 2-methylcitrate and reveal a unique bacterial metabolic detoxification strategy, highlighting the value of PrpD as a potential anti-bacterial target.